Disk-laser Welding of Ti-6Al-4V Titanium Alloy Plates in T-joint Configuration. (2017) - Caiazzo, F.; Cardaropoli, F.; Alfieri, V.; Sergi, V.; Argenio, P.; Barbieri, G.
Abstract: Titanium alloys are employed in a wide range of applications, ranging from aerospace to medicine. In particular, Ti-6Al-4V is the most common, thanks to an excellent combination of low density, high specific strength and corrosion resistance. Laser welding has been increasingly considered as an alternative to traditional techniques to join titanium alloys. An increase in penetration depth and a reduction of possible welding defects is indeed achieved; moreover a smaller grain size in the fused zone is benefited in comparison to either TIG and plasma arc welding, thus providing an increase in the tensile strength of the welded structures. The aim of this work is to study disk-laser welding of 3.2mm thick Ti-6Al-4V plates in T-joint configuration without using a filler wire, defining the influence of different process parameters. The issue concerning the clamping of the plates is discussed and a proper device is developed to carry out welds. A structured plan has to be carried out in order to characterize the process thus discussing the response variables. Power and welding speed are considered as crucial input variables since they determine the thermal input to the work-piece; furthermore, given the particular configuration analyzed, tilt angle is considered as a further variable, whereas focus position is fixed below the upper surface to obtain a full penetration. Welding beads have been first examined with a coordinate measuring machine to study distortions, and then from a morphological point of view. Eventually, Vickers microhardness testing has been conducted to discuss structural changes in fusion and heat affected zone due to welding thermal cycles.